High expression of glutamate‐ammonia ligase is associated with unfavorable prognosis in patients with ovarian cancer. Issue 7 (25th March 2018) - Fan, Shaohua; Wang, Yanyan; Zhang, Zifeng; Lu, Jun; Wu, Zhiyong; Shan, Qun; Sun, Chunhui; Wu, Dongmei; Li, Mengqiu; Sheng, Ning; Xie, Ying; Zheng, Yuanlin
Abstract: Glutamate‐ammonia ligase (GLUL), which is also called GS (glutamine synthetase), is the enzyme that catalyzes the synthesis of glutamine from glutamate and ammonia in an ATP‐dependent reaction. Here, we found higher expression of GLUL in the ovarian cancer patients was associated with worse disease‐free survival (DFS) and overall survival (OS). In addition, GLUL was heterogeneously expressed in various ovarian cancer cells. The mRNA and protein expression levels of GLUL in NIH:OVCAR‐3 and ES‐2 cells were obviously higher than that in the other types of ovarian cancer cells. Knockdown of GLUL in NIH:OVCAR‐3 or ES‐2 cells could significantly decrease the proliferation ability. Furthermore, GLUL knockdown markedly inhibited the p38 MAPK signaling pathway in NIH:OVCAR‐3 or ES‐2 cells. Our findings suggest that decreasing expression of GLUL may be a new approach that can be used for ovarian cancer treatment. Abstract : We found higher expression of GLUL in the ovarian cancer patients was associated with worse disease‐free survival (DFS) and overall survival (OS). Our findings suggest that decreasing expression of GLUL may be a new approach that can be used for ovarian cancer treatment.